3,8-Bis(4-chlorophenyl)-4,7-dimethyltricyclo[4.2.2.0(2,5)]deca-3,7-diene - Tomura, Masaaki (International Union of Crystallography, 2008)
The title tricyclic diene, C(24)H(22)Cl(2), is the product of thermal ring-opening of a corresponding basketane (pentacyclo[4.4.0.0(2,5).0(3,8).0(4,7)]decane) derivative. The cyclobutene ring is planar to within 0.0032 (12) Å and its geometry is normal. The two 4-chlorophenyl groups are oriented in an approximately face-to-face conformation with a dihedral angle of 44.14 (6)° between them. The 4-chlorophenyl group bonded to the cyclobutene ring lies almost in the plane of the cyclobutene ring, with a dihedral angle of 8.29 (17)° between the ring planes. The average intramolecular C⋯C distance between the two C=C bonds is 2.92 Å. In the crystal structure, the molecules are well separated with no close C—H⋯Cl or C—H⋯π intermolecular interactions.